Coexistence of ulcerative colitis and neurofibromatosis type 1: a case report and literature review - Huang, Xiuqiang; Lyu, Shuhua; Zhong, Jin; Li, Yiming; Zhao, Luyao; Sun, Manyi (Frontiers in Medicine, 2025)
BackgroundNeurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder resulting from mutations in the NF1 gene, while ulcerative colitis (UC) is a chronic inflammatory disease of the intestines with an unclear etiology. Herein, we report a case involving an elderly male patient with both UC and NF1.Case presentationThe patient experienced chronic diarrhea and mucopurulent bloody stools, leading to a confirmed diagnosis of UC through colonoscopy and histopathological examination. Treatment with corticosteroids, vedolizumab, and five-flavor sophora flavescens enteric-coated capsules (SFEC), a traditional Chinese medicine, successfully achieved remission. During the physical examination, the patient exhibited axillary café-au-lait spots, scoliosis, and multiple subcutaneous nodules on the head, trunk, and limbs. Imaging and histopathological analysis identified these nodules as neurofibromas, fulfilling the diagnostic criteria for NF1. Key features of this case include the steroid-dependent nature of the UC, which significantly improved with the combination therapy of vedolizumab and SFEC, as well as the presence of neurofibromas affecting the intestines and greater omentum. Furthermore, colonic ulcers and polypoid lesions may have been linked to the neurofibromas, while histopathological findings in both skin and intestinal tissues indicated the involvement of mast cells. This case illustrates the intricate relationship between UC and NF1, supporting a common inflammatory mechanism that may involve mast cells.ConclusionThis case highlights the importance of clinicians being aware of the rare coexistence of UC and NF1 to ensure accurate diagnosis and appropriate management.